Study of the antimutagenic effects of plant polyphenols under the action of genotoxicants - Ivanov, V. S. (Journal of Education, Health and Sport, 2019)
In the test of dominant lethal germ cell mutations in male rats, the effect of phenobarbital and fluorouracil genotoxicants and their combined administration with the biotrit-C preparation, obtained from wheat seedlings and containing plant polyphenols, was studied. For the first time, high mutagenicity of fluorouracil and pronounced antimutagenic properties of the preparation Biotrit-C were established.